Strategy for Internalizing the Value of Religious Moderation in Elementary School Students - Ruswan Ruswandi; Endi Suhendi (At Turots: Jurnal Pendidikan Islam, 2025)
Education on religious moderation values from an early age plays a crucial role in shaping children’s character to be tolerant, inclusive, and respectful of differences. This study aims to explore strategies for internalizing religious moderation values in elementary school students through a holistic approach involving curriculum, interactive learning methods, teacher role models, school environment, and parental and community involvement. A qualitative case study approach was employed, utilizing participatory observation, in-depth interviews, and document analysis. Data were analyzed using content and thematic analysis, and validity was ensured through triangulation, member checking, and peer debriefing. The findings indicate that the internalization of religious moderation values can be carried out through curriculum integration, varied and interactive teaching methods, creation of a conducive school environment, active parental and community involvement, as well as habituation and teacher exemplification. The internalization model can be implemented individually, in groups, or in a classroom setting, covering I’tiqodiyah, Khuluqiyah, and Amaliyah aspects, thereby fostering students’ moderate, responsible, and ethical character. This study provides practical implications for teachers, school principals, parents, and educational stakeholders in designing comprehensive and sustainable character education strategies based on religious moderation